Harnessing Economic Impacts of Migrant Remittances for Development in Sub-Saharan Africa: A Critical Review of the Literature - Nyasulu, Themba (African Human Mobility Review, 2021)
The recent rise in migrant remittances across Sub-Saharan Africa is one of the important issues currently dominating economic policy discourse in the region. Given the large volume of remittance flows, it is obvious that they have important positive and negative economic effects on the individual families and economies that receive them. Therefore, this paper critically examines channels through which remittance transfers affect microeconomic and macroeconomic activity, and suggests policy options available to Sub-Saharan African countries in terms of harnessing their development potential. The paper affirms that prospects for remittances to facilitate economic development remain high provided that recipient countries put in place institutional frameworks capable of mitigating the malign effects and enhancing the benign effects of remittances.